Perlindungan Hukum Bagi Pasien Vaksin Palsu Yang Merugikan Konsumen Rumah Sakit - Nabila Ahzahra; Rani Apriani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Humans in general are social beings, namely interacting with one another in order to complement their individual needs. Health is also an element of general welfare that must be realized in accordance with the national goals of the Indonesian nation. In essence, the fulfillment of health needs can be obtained from other parties in a reciprocal way so that in health services, patients as recipients of medical assistance and doctors as providers of medical assistance and health workers to operate medical devices are very regrettable with the many crimes in the world of health that very detrimental, one of which is the circulation of fake children's vaccines which began in 2016 when a victim who was still a toddler died after being injected with the vaccine. For this reason, given the importance of legal protection that protects consumers or patients and the importance of the form of accountability of business actors as hospitals.